Antiviral activity of tenofovir against Cauliflower mosaic virus and its metabolism in Brassica pekinensis plants - Spak, Josef; Votruba, Ivan; Pavingerová, Daniela; Holý, Antonín; Spaková, Vlastimila; Petrzik, Karel (Antiviral research, 2011)
The antiviral effect of the acyclic nucleoside phosphonate tenofovir (R)-PMPA on double-stranded DNA Cauliflower mosaic virus (CaMV) in Brassica pekinensis plants grown in vitro on liquid medium was evaluated. Double antibody sandwich ELISA and PCR were used for relative quantification of viral protein and detecting nucleic acid in plants. (R)-PMPA at concentrations of 25 and 50 mg/l significantly reduced CaMV titers in plants within 6-9 weeks to levels detectable neither by ELISA nor by PCR. Virus-free plants were obtained after 3-month cultivation of meristem tips on semisolid medium containing 50 mg/l (R)-PMPA and their regeneration to whole plants in the greenhouse. Studying the metabolism of (R)-PMPA in B. pekinensis revealed that mono- and diphosphate, structural analogs of NDP and/or NTP, are the only metabolites formed. The data indicate very low substrate activity of the enzymes toward (R)-PMPA as substrate. The extent of phosphorylation in the plant's leaves represents only 4.5% of applied labeled (R)-PMPA. In roots, we detected no radioactive peaks of phosphorylated metabolites of (R)-PMPAp or (R)-PMPApp.
Keywords: Adenine; Viral Load; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA virů; adenin; antivirové látky; Caulimovirus; Organophosphonates; biotransformace; Biotransformation; ELISA; Viral Proteins; Tenofovir; Brassica; DNA, Viral; virová nálož; virové proteiny; Enzyme-Linked Immunosorbent Assay; Antiviral Agents; tenofovir; organofosfonáty